2010
DOI: 10.1016/j.brainres.2010.02.084
|View full text |Cite
|
Sign up to set email alerts
|

Word and pseudoword superiority effects reflected in the ERP waveform

Abstract: A variant of the Reicher-Wheeler task was used to determine when in the event-related potential (ERP) waveform indices of word and pseudoword superiority effects might be present, and whether ERP measures of superiority effects correlated with standardized behavioral measures of orthographic fluency and single word reading. ERPs were recorded to briefly presented, masked letter strings that included real words (DARK/PARK), pseudowords (DARL/PARL), nonwords (RDKA/RPKA), and letter-in-xs (DXXX, PXXX) stimuli. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
74
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(100 citation statements)
references
References 102 publications
(173 reference statements)
14
74
1
2
Order By: Relevance
“…The other half of the items corresponded to strings made of sub-lexical units (i.e., bigrams) that were legal in both of their languages (i.e., orthographically unmarked words). First, in line with previous evidence, we found that letter recognition was significantly faster and more accurate for words than non-words (i.e., the word superiority effect; see Coch & Mitra, 2010;Grainger et al, 2003;Grossi et al, 2008;McClelland, 1976, among others). This effect was not modulated by orthographic markedness (i.e., language-common or language-specific orthography) but we found that letters embedded in strings that respect the orthotactic rules of both languages (i.e., unmarked language-unspecific strings) were recognized faster and more accurately than letters embedded in strings containing language-specific sub-lexical cues (namely, an orthographic markedness effect).…”
supporting
confidence: 91%
“…The other half of the items corresponded to strings made of sub-lexical units (i.e., bigrams) that were legal in both of their languages (i.e., orthographically unmarked words). First, in line with previous evidence, we found that letter recognition was significantly faster and more accurate for words than non-words (i.e., the word superiority effect; see Coch & Mitra, 2010;Grainger et al, 2003;Grossi et al, 2008;McClelland, 1976, among others). This effect was not modulated by orthographic markedness (i.e., language-common or language-specific orthography) but we found that letters embedded in strings that respect the orthotactic rules of both languages (i.e., unmarked language-unspecific strings) were recognized faster and more accurately than letters embedded in strings containing language-specific sub-lexical cues (namely, an orthographic markedness effect).…”
supporting
confidence: 91%
“…It thus seems that the adult's brain is sensitive to the dependencies among letters and positions within word-forms (sublexical orthographic units) in a very early stage of the reading process, as early as 80-120 ms after stimulus onset. Recent studies have already suggested neurophysiological correlates of sublexical orthographic processing in similar latency ranges (Coch & Mitra, 2010;Hauk, Davis, Ford, Pulvermüller, & Marslen-Wilson, 2006;, although using other measures of orthotactic constrains like tri-/bigram frequency. Our results add to these studies indicating that orthographic typicality assessed both in terms of letter position frequency and sequential constraints can modulate early ERP responses of visual word recognition.…”
Section: Discussionmentioning
confidence: 99%
“…These findings have commonly been interpreted as reflecting a facilitated access to lexical orthographic information for familiar words between 100 and 200 ms. Finally, other studies have described an effect of orthographic sublexical regularity as early as 100 ms, and localized into left inferior temporal areas (Coch & Mitra, 2010;. For example, atypical items quantified by bigram or trigram frequencies elicit more brain activity than typical ones , which suggests that orthographic structure processing is under way at this time frame; but other measures of orthotactic dependencies such as sequential constrains still need to be tested.…”
Section: Introductionmentioning
confidence: 96%
“…It therefore appears that we have three studies showing effects emerging between 200-250 ms post-stimulus onset in a letter search task (Ziegler et al, 1997), a letter-in-string identification task (Massol et al, 2011), and a lexical decision task (Massol et al, 2011;Rosazza et al, 2009), plus one study showing later effects in a rhyme judgment task (Bentin et al, 1999), and one study showing an earlier effect in a letter-in-string identification task (Coch & Mitra, 2010). Results from studies comparing word stimuli with random consonant strings are also in line with this general tendency (McCandliss et al, 1997;Martin et al, 2006).…”
Section: Pronounceable Nonwords Vs Consonant Stringsmentioning
confidence: 99%
“…These authors observed a more negative waveform for words than nonwords over the left temporoparietal regions. More recently, Coch and Mitra (2010) tested pronounceable nonwords and consonant string stimuli in the Reicher-Wheeler task with ERP recordings. They found that consonant strings produced more positive-going waveforms than pronounceable stimuli (words and pronounceable nonwords) starting around 150 ms poststimulus onset.…”
Section: Erps and Word/pseudoword Superioritymentioning
confidence: 99%